Leo Strauss on Plato's Euthyphro : the 1948 notebook, with lectures and critical writings - Strauss, Leo; Kerber, Hannes, 1987-; Minkov, Svetozar, 1975- (University Park, Pennsylvania : The Pennsylvania State University Press, 2023)
"An examination of Leo Strauss's 1948 notebook and other writings on the Euthyphro, Plato's dialogue on piety, using close analysis and line-by-line commentary"--
Introduction : the significance of Strauss's notebook on Plato's Euthyphro / Hannes Kerber and Svetozar Y. Minkov -- Strauss's notebook on Plato's Euthyphro and Crito -- Strauss's lecture "On Plato's Euthyphron" -- Reading Strauss's notebook on Plato's Euthyphro / Hannes Kerber -- Comments on Strauss's notes on the Crito / Svetozar Y. Minkov -- An introduction to Strauss's "On Plato's Euthyphron" / Wayne Ambler -- Translation of Plato's Euthyphro / Seth Bernardete.
Includes the text of Plato's Euthyphro in Greek with English translation.
Includes bibliographical references (pages [219]-223) and indexes.
English text, partially translated from the Ancient Greek.
Print version record.
JSTOR
Keywords: Plato; Euthyphro (Plato); Piety; Piété.; PHILOSOPHY / Political; Piety; .; Crito; Euthyphro; Jerusalem and Athens; Leo Strauss; Plato; Seth Benardete; Socrates; ancient philosophy; classical political philosophy; hermeneutics; neoconservativism; philosophy of religion; philosophy; piety; religion; theology